Uncovering the City of London Corporation: Territory and temporalities in the new state capitalism. (February 2023) - Eagleton-Pierce, Matthew
The heterogenous literature on the 'new state capitalism' has provoked considerable academic and popular interest in recent years, but also critique regarding how to analytically bolster the concept and enhance empirical understanding. This paper responds toAlami and Dixon's (2020a, 2020b ) call for a fresh interrogation of the new state capitalism through an examination of the governance of the City of London. As the largest exporter of financial services in the world, the City plays a crucial role in the reproduction of financial capitalism. However, one major deficiency in debates on the political governance of the City surrounds the role of sub-state institutions. Remarkably, with limited exceptions, we know comparatively little about the main municipal authority: the City of London Corporation. As a local governing body, it conducts all the ordinary work of a public authority. But the Corporation also has many peculiar features which distinguish it from other public institutions, including vigorous support of financial services through planning law, lobbying and other promotion. This paper argues that thinking on the new state capitalism offers a vehicle for dissecting how the Corporation operates in the service of transnational financial interests. By unpacking how the Corporation is tied into a web of relations with private finance and other historically developed networks of power, the discussion problematises two macro themes on the new state capitalism: the spatial complexity of multi-scalar state governance and the temporal fluidity of legacies of the past interpenetrating with the present definition of 'now'.